Childhood vaccination coverage in Brazil and the impact of the COVID-19 pandemic: An integrative review (Research, Society and Development, 2026)
Objective: Describe the impact of the COVID-19 pandemic on childhood vaccination coverage in Brazil. Methodology: This is an integrative literature review, based on a survey of the Bireme, Pubmed and Scielo databases, using the descriptors “Vaccination Coverage” OR “Vaccination Coverage” AND “COVID-19” OR “SARS-CoV-2” AND “Brazil” OR “Brazil”; articles between 2021 and 2023 in English and Portuguese. Results: The research found 31.589 articles, of which 12 were selected according to the aspects of inclusion in association with the guiding question. The research revealed a falling rate of the childhood vaccination coverage originating from a pre-pandemic context, but also disclosed that the decrease has been intensified with it and lasts even after this event. This result demonstrates the multifactorial causes that interfere with the decision to vaccinate children in Brazil. Conclusion: The COVID-19 pandemic has reduced childhood vaccination coverage in Brazil, especially in vulnerable regions. It can be said that vaccine hesitancy and misinformation were some of the contributing factors. To reverse the situation, it is essential to maintain immunization campaigns and adopt strategies such as mobile units in affected areas and funding to expand vaccination.